Health professionals knowledge of telemedicine and its associated factors working at private hospitals in resource-limited settings - Wubante, Sisay Maru; Tegegne, Masresha Derese (Frontiers in Digital Health, 2022)
Introduction The appropriate implementation of telemedicine in the healthcare system has the potential to overcome global problems such as accessibility and quality healthcare services. Thus assessing the knowledge of health professionals before the actual adoption of telemedicine is considered a prominent solution to the problems. Objective This study aimed to assess healthcare professionals' knowledge of telemedicine and its associated factors at private hospitals in low-resource settings. Method An institution-based cross-sectional study was conducted among 423 health professionals at private hospitals in low-income settings in Ethiopia, from March to April 2021. Data collection was performed by pretested and self-administered questionnaires. This study employed statistical packages for social sciences software. This study employed multivariable logistic regression to determine dependent and independent variables associated with adjusted odd ratio and 95% CI. Result in this study about 65.8% of health professionals have good knowledge on Telemedicine .Computer literacy (AOR = 2.9; 95% CI: 1.8, 4.6), computer training (AOR = 2.0; 95% CI: 1.2, 3.3), Internet availability at workplace (AOR = 2.1; 95%CI: 1.3, 3.4), had private laptop (AOR = 1.7; 95% CI: 1.1, 2.9) were significantly associated with knowledge. Conclusion and recommendation In general health professionals had good knowledge of Telemedicine. Inclusive packages of capacity by training among health providers are fundamental for the successful implementation of telemedicine.